2012
DOI: 10.1002/jcb.24159
|View full text |Cite
|
Sign up to set email alerts
|

N‐(4‐hydroxyphenyl)retinamide inhibits breast cancer cell invasion through suppressing NF‐KB activation and inhibiting matrix metalloproteinase‐9 expression

Abstract: Synthetic retinoid N-(4-hydroxyphenyl)retinamide (4-HPR) has been reported to exhibit anti-invasive and anti-metastatic activities by suppressing the enzymatic activity of matrix metalloproteinase (MMP)-9, but the underlying mechanism remains unclear. Here, we show that 4-HPR blocks the activity of MMP-9 in two ways: by reducing phorbol 12-myristate 13-acetate (PMA)-induced MMP-9 secretion and by suppressing cell invasion through the downregulation of MMP-9 gene transcription in MCF-7 breast cancer cells. 4-HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Also, it has been proven as a regulator of MMP-9 to promote tumor invasion and metastasis [29, 30]. In addition, Akt signaling regulates the expression of NF-κB as well as MMP-9 in several cancer cells [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been proven as a regulator of MMP-9 to promote tumor invasion and metastasis [29, 30]. In addition, Akt signaling regulates the expression of NF-κB as well as MMP-9 in several cancer cells [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are critical enzymes that digest basement membrane proteins during migration [36,37], but their function in the netrin signaling pathway remain largely unknown. Interestingly, we found that Ntn-1 uniquely increased MMP-12 expression via NF-kB activation in promoting UCB-MSCs motility.…”
Section: Effect Of Netrin-1 On Human Ucb-msc Motilitymentioning
confidence: 99%
“…Involvement in metastasis has been implicated in all of these pathways. NF-kappa B has been shown to be important for promoting migration and metastasis [10] and upregulating the expression of matrix metalloproteinases, urokinase-type plasminogen activator, and cytokines in highly metastatic cancer cell lines [11-13]. In contrast, although JNK is important in inflammation, proliferation, and apoptosis, it also regulates cell migration by maintaining the labile adhesions required for rapid cell migration [14,15].…”
Section: Introductionmentioning
confidence: 99%